Rapid Identification of SARS-CoV-2 Omicron BA.5 Spike Mutation F486V in Clinical Specimens Using a High-Resolution Melting-Based Assay - Aoki, Akira; Adachi, Hirokazu; Mori, Yoko; Ito, Miyabi; Sato, Katsuhiko; Kinoshita, Masayoshi; Kuriki, Masahiro; Okuda, Kenji; Sakakibara, Toru; Okamoto, Yoshinori; Jinno, Hideto (Viruses, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron subvariant BA.5 emerged as of February 2022 and replaced the earlier Omicron subvariants BA.1 and BA.2. COVID-19 genomic surveillance should be continued as new variants seem to subsequently appear, including post-BA.5 subvariants. A rapid assay is needed to differentiate between the currently dominant BA.5 variant and other variants. This study successfully developed a high-resolution melting (HRM)-based assay for BA.4/5-characteristic spike mutation F486V detection and demonstrated that our assay could discriminate between BA.1, BA.2, and BA.5 subvariants in clinical specimens. The mutational spectra at two regions (G446/L452 and F486) for the variant-selective HRM analysis was the focus of our assay. The mutational spectra used as the basis to identify each Omicron subvariant were as follows: BA.1 (G446S/L452/F486), BA.2 (G446/L452/F486), and BA.4/5 (G446/L452R/F486V). Upon mutation-coding RNA fragment analysis, the wild-type fragments melting curves were distinct from those of the mutant fragments. Based on the analysis of 120 clinical samples (40 each of subvariants BA.1, BA.2, and BA.5), this method’s sensitivity and specificity were determined to be more than 95% and 100%, respectively. These results clearly demonstrate that this HRM-based assay is a simple screening method for monitoring Omicron subvariant evolution.